Identification of pel, a Streptococcus pyogenes Locus That Affects both Surface and Secreted Proteins - Li, Zhuqing (American Society for Microbiology, 1999)
A Tn917 insertion mutant of an M49 serotype, opacity factor-positive Streptococcus pyogenes, was isolated. It had the following phenotypes: decreased β-hemolysis mediated by streptolysin S, reduction in the activity of a secreted cysteine protease and streptokinase, and an altered immunoglobulin and fibrinogen-binding phenotype. The site of insertion of Tn917 into the chromosome and the surrounding sequence, the pel region (pleiotropic effect locus), was determined. Phage A25 transduction confirmed that the pleiotropic changes in phenotype could be cotransduced with Tn917. The pel region was cloned and sequenced, and the transposon was found to be inserted upstream of a single open reading frame which led to a failure to transcribe a 500-base mRNA. The loss of this transcript decreased the transcription of emm and speB genes and reduced the secretion of streptokinase. Enhanced Pel expression from a nisin-inducible plasmid resulted in increased message levels for emm in a wild-type organism. Characterization of the pel mutant provides evidence for the coordinated regulation of secreted and surface proteins and suggests the existence of a new global regulatory factor in S. pyogenes.